Use Of Medications Is Strongly Associated With Worse Self-Perceived Health In Institutionalized And Community-Dwelling Elderly - Fernanda Nascimento Costa; Liciana Vaz de Arruda Silveira; Alessandro Ferrari Jacinto (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: This study aimed to investigate self-perceived health among a sample of institutionalized and a sample of communitydwelling elderly in two cities of the São Paulo State, Brazil: Bauru and Botucatu. METHODS: Ninety-five elderly individuals from ten long-term care homes from Bauru, SP and Botucatu, SP and 101 community-dwelling elderly users of three centers for the elderly in Bauru, SP were assessed. After obtaining the personal and health data, the evaluation of self-perception of health was performed by asking how the elderly person perceived his health in the most recent days; the response options were very poor, poor, fair, good or excellent. RESULTS: There was a statistically significant difference (< 0.001) between institutionalized and community-dwelling elderly considering self-perceived health.. After adjusting the model of ordinal logistic regression, it was observed that institutionalized individuals who regularly used prescription medications had a chance 7.5 times greater than nonusers of having a worse self-perceived health [OR = 7.5; 95%CI (2.1-26.6; p = 0.002)]. In the community-dwelling group it was observed that individuals who regularly used prescription medications had a chance 4.5 times greater than nonusers of having a worse self-perceived health [OR = 4.5; 95%CI (1.5-13.7; p = 0.008)]. CONCLUSIONS: Worse self-perceived health was associated with taking prescription medications among both institutionalized and community-dwelling elderly.